2022
DOI: 10.3390/ijms23094477
|View full text |Cite
|
Sign up to set email alerts
|

Update on Glycosphingolipids Abundance in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most frequent type of primary liver cancer. Low numbers of HCC patients being suitable for liver resection or transplantation and multidrug resistance development during pharmacotherapy leads to high death rates for HCC patients. Understanding the molecular mechanisms of HCC etiology may contribute to the development of novel therapeutic strategies for prevention and treatment of HCC. UDP-glucose ceramide glycosyltransferase (UGCG), a key enzyme in glycosphingolipid metabo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…The UGCG gene encodes UDP-glucose ceramide glucosyltransferase, representing the initial crucial step in the biosynthesis of the majority of glycosphingolipids. These lipids play a vital role as components within membrane microstructural domains, facilitating membrane translocation and signal transduction processes [ 33 ]. Naoki Seito et al found that specific knockdown of UGCG in mouse chondrocytes resulted in more severe pathological OA induced by destabilization surgery and similarly more severe cartilage degradation induced by IL-1α in vitro experiments [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The UGCG gene encodes UDP-glucose ceramide glucosyltransferase, representing the initial crucial step in the biosynthesis of the majority of glycosphingolipids. These lipids play a vital role as components within membrane microstructural domains, facilitating membrane translocation and signal transduction processes [ 33 ]. Naoki Seito et al found that specific knockdown of UGCG in mouse chondrocytes resulted in more severe pathological OA induced by destabilization surgery and similarly more severe cartilage degradation induced by IL-1α in vitro experiments [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, gangliosides, a subtype of glycosphingolipids prevalent on cell surfaces, particularly abundant in the nervous tissues of various animals [17], play a pivotal role in cell functions like proliferation, adhesion, migration, and interactions within the cell microenvironment in different cancers [18][19][20][21]. Expression patterns and the underlying mechanisms of gangliosides in normal and cancer cells have been explored by several researchers [22][23][24]. Notably, human melanomas predominantly feature ganglioside GM3 and GD3 on their cell surfaces [25].…”
Section: Introductionmentioning
confidence: 99%